Innovative Tokyo - Fujita, Kuniko, 1944- 1944- (Policy research working paper, 2005)
"Fujita and Hill compare and contrast Tokyo's innovation structure with the industrial districts model and the international hub model in the literature on urban and regional development. The model embraces and yet transcends both industrial districts and international hub models. The authors provide key elements making up the Tokyo model--organizational knowledge creation, integral and co-location systems of corporate research and development and new product development, test markets, industrial districts and clusters, participative consumer culture, continuous learning from abroad, local government policies, the national system of innovation, and the historical genesis of Tokyo in Japan's political economy. They find that the Tokyo model of innovation will continue to evolve with the changing external environment, but fundamentally retain its main characteristics. The lessons from the Tokyo model is that openness, a diversified industrial base, the continuing development of new industries, and an emphasis on innovation all contribute to the dynamism of a major metropolitan region. This paper--a product of the Development Research Group--was prepared for the East Asia Prospect Study"--World Bank web site